2018
DOI: 10.26633/rpsp.2018.66
|View full text |Cite
|
Sign up to set email alerts
|

Open data and public health

Abstract: This article provides an overview of the intersection of open data and public health by first defining open government data, public health data, and other key concepts and relevant terminologies. There are differing perceptions on the urgency and importance of the openness of public health data. It has been established that disease outbreaks such as happened during the Ebola and Zika virus epidemics are indicative of the need for countries to develop a framework that will provide guidance for the management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
(16 reference statements)
0
24
0
2
Order By: Relevance
“…Thus, it has been reported that data sharing was important during the influenza virus A subtype H1N1 epidemic of 2009; however, it was not as significant with the Middle East Respiratory Syndrome (MERS) epidemic, first reported in Saudi Arabia in 2012, and the Ebola epidemics in 2014–2016, which revealed gaps in the open availability of the genetic sequences of the virus (Yozwiak et al, 2015 ). The Ebola, dengue and Zika epidemics have evidenced the need to develop infrastructures for the proper management of data of interest to public health (D’Agostino et al, 2018 ), as well as the establishment of codes of conduct that should govern the exchange of data on new biological threats (Capua, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been reported that data sharing was important during the influenza virus A subtype H1N1 epidemic of 2009; however, it was not as significant with the Middle East Respiratory Syndrome (MERS) epidemic, first reported in Saudi Arabia in 2012, and the Ebola epidemics in 2014–2016, which revealed gaps in the open availability of the genetic sequences of the virus (Yozwiak et al, 2015 ). The Ebola, dengue and Zika epidemics have evidenced the need to develop infrastructures for the proper management of data of interest to public health (D’Agostino et al, 2018 ), as well as the establishment of codes of conduct that should govern the exchange of data on new biological threats (Capua, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is likely to facilitate the participation of surveillance agencies in the development of a CBMIS, whereas these agencies would be “reluctant to abandon their own data schemata in favor of a standard schema supplied by someone else” [ 20 ]. In that sense, the proposed approach differs from recommendations provided in D’Agostino et al [ 22 ] to facilitate data sharing in public health, which include the development of regional frameworks that “can be adopted or adapted by each country through national or subnational policies” as a prerequisite for the realization of data interoperability.…”
Section: Discussionmentioning
confidence: 93%
“…Cross-sectional researches in preschool and school children and their parents showed that parents whoare physically active, are more likely to support their children’s engagement in physical activity [ 36 , 37 ]. Possible mechanisms for the relationship between parents’ and child’s activity levels include the parents’ serving as role models, enhancement and support by active parents of their child’s participation in physical activity, and genetically transmitted factors that predispose the child to be more physically active [ 38 ].Furthermore, the Greek family fits the ‘Mediterranean model’and consequently, it shares similar socio-demographic characteristics with other Mediterranean countries, meaning that traditional values and roles (marriage, family ties) are prevalent [ 39 ]. Thus, parents have a sound effect on their children’s every day habits.…”
Section: Discussionmentioning
confidence: 99%